2012
DOI: 10.1111/aji.12043
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Sexual Debut a Risk Factor for HIV Infection Among Women in Sub‐Saharan Africa? A Systematic Review

Abstract: CitationSt€ ockl H, Kalra N, Jacobi J, Watts C. Is early sexual debut a risk factor for hiv infection among women in sub-Saharan Africa? A systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 36 publications
5
86
0
1
Order By: Relevance
“…The overall results showed that HIV risk was higher among currently and previously married individuals, low circumcision rates and high-risk sexual behaviours. These findings are consistent with those observed in previous studies based on DHS data [12,14,17,39,41,44]. A possible explanation for increased likelihood for HIV infections among divorced/separated individuals could be that previously married individuals tend to have more sexual partners than single or married individuals [45].…”
Section: Discussionsupporting
confidence: 92%
“…The overall results showed that HIV risk was higher among currently and previously married individuals, low circumcision rates and high-risk sexual behaviours. These findings are consistent with those observed in previous studies based on DHS data [12,14,17,39,41,44]. A possible explanation for increased likelihood for HIV infections among divorced/separated individuals could be that previously married individuals tend to have more sexual partners than single or married individuals [45].…”
Section: Discussionsupporting
confidence: 92%
“…These include risky sexual behaviours such as multiple partners, sex under the influence of alcohol or drugs, unplanned pregnancy and sexually transmitted infections (STIs), including HIV. [1][2][3] Early sexual debut not only increases risks to sexual and reproductive health but is also associated with experiences of sexual coercion. [4][5][6] Sexual coercion has been defined as the act of forcing (or attempting to force) another individual, through violence, threats, verbal insistence, deception, cultural expectations or economic circumstances, to engage in sexual behaviour against his or her will.…”
mentioning
confidence: 99%
“…This association may suggest biologic susceptibility during physical development, high-risk sexual behaviours and lack of access to or low use of condoms at a young age, and/or an association with duration of sexual activity [33,34]. Likewise, the association of prevalent HIV infection with older current age may be due to higher cumulative risk exposures for acquisition of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the association of prevalent HIV infection with older current age may be due to higher cumulative risk exposures for acquisition of HIV. However, estimating the duration of sexual activity is challenging as sexual behaviours are not static, but vary across the life course and as partnerships change [34]. While study-related factors such as low power and potential misclassification of behaviours may partially explain insignificant findings, broader factors such as high background prevalence of HIV in the MSM population [35], biologic susceptibility of rectal mucosa [36] and network-level characteristics may also be more determinative in driving HIV transmission and acquisition risks among these men [35,37].…”
Section: Discussionmentioning
confidence: 99%